1966 and All That: James Gibson and Bottom-Down Theory. Issue 3 (3rd July 2017) - Costall, Alan
ABSTRACT: The "later" James Gibson is widely misrepresented as an extreme stimulus–response theorist. In fact, Gibson's 1966 book presents a radical alternative to stimulus–response theory. "Perceptual systems" are not passive and receptive but "organs of active attention" (1966/1968, p. 58). Perceivers "reach out" into the world. This commentary examines some of the implications of Gibson's systems-cum-functionalist-cum-ecological approach, including the relations between the senses; the concept of "sensationless" perception; and most fundamentally, the nature of perceptual systems as extending beyond the body. I conclude that an adequate understanding of perception cannot be limited to the already severely limited domain of psychology. If Gibson is right, "ecological psychology" is a contradiction in terms.